PEMANFAATAN KONSORSIA MIKROORGANISME SEBAGAI AGEN BIOREMEDIASI UNTUK MEREDUKSI AMONIA PADA MEDIA PEMELIHARAAN UDANG WINDU (Penaeus monodon Fabricius) - UMROH UMROH (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2007)
Ammonia is a toxic compound can endanger the shrimp. The main source of ammonia in the shrimp pound derives from an eaten food and shrimp’s faeces. High ammonia concentration can causes death, therefore the existence of ammonia should be controlled. One of alternatives to overcome it is by using bioremediation technic with microorganism consortia. The aims of this research are to test the ability of microorganism consortia in reducing ammonia and to test the ability of microorganism consortia against the life passing and to test the ability of microorganism consortia against the water quality. This research was conducted in September - October 2002, took place in Algae Laboratory of Oceanography Marine Station Teluk Awur, Jepara and ammonia analysis was conducted in Physics-Chemistry Laboratory, the Brackish Water Cultivation Bureau, Jepara. The method used in this research was experimental method with complete random approach. There were 4 treatment, namely the giving of microorganism consortia in the amount of 1,53 x 1010 coloni, 3,06 x 1010 coloni, 6,12 x 1010 coloni and control. The observed parameter were ammonia degree, DO, temperature, salinity, pH, life passing, and the windu shrimp’s behaviour.